2011
DOI: 10.21608/ejabf.2011.2101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some medicinal plants diets on the mono-sex Nile Tilapia (Oreochromis niloticus), growth performance, feed utilization and some physiological parameters

Abstract: he effects of diets supplemented with six different medical plants (fenugreek meal (FM), (Trigonella foenum-graecum); fenugreek sprouts meal (FSM); eucalyptus fresh leaves (EFL), (Eucalyptus citriodora); hot pepper meal (HPM) (Capsicum frutescens L. var. abbreviatum); thyme seeds meal (TSM) (Thymus vulgaris) and chamomile flowers meal (CFM), (Matricaria recutita L) at three levels (0.00; 1.00 and 2.00 %) on the growth performance, feed utilization and whole body composition and some physiological parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…() who reported that the fenugreek seed as feed additive improved growth parameters (body weight, weight gain and specific growth rate) in Nile tilapia fingerlings. This observation is also in agreement with the finding of Tonsy, Mahmoud, Labib and Zaki ().…”
Section: Discussionsupporting
confidence: 93%
“…() who reported that the fenugreek seed as feed additive improved growth parameters (body weight, weight gain and specific growth rate) in Nile tilapia fingerlings. This observation is also in agreement with the finding of Tonsy, Mahmoud, Labib and Zaki ().…”
Section: Discussionsupporting
confidence: 93%
“…In another study, Al-Safah and Al-Faragi ( 2017) found the highest growth rate in Common carp fingerlings that were fed a diet containing 1.5% thyme. However, the results of Tonsy et al (2011) showed that Nile tilapia fingerlings had the best performance when fed diets containing 1-2% fenugreek sprouts. These variations in results can be attributed to the changes of fish species, life stages, levels, and types of herbal plants used.…”
Section: Discussionmentioning
confidence: 96%
“…Essential oils and extracts obtained from medicinal and aromatic plants improve the growth performance, utilization of the feed, the flavor of the feed, have a stimulating effect on the efficiency of pancreatic enzymes and bile secretion, accelerate the regeneration of epithelial cells in the small intestine and increase the absorption of nutrients by establishing the microflora balance, and prevent the adhesion of harmful microorganisms to intestinal epithelial cells. It is reported that it prevents them from settling in the system and gives strength to the immune system (Karasu and Öztürk, 2014;Khalafalla, 2009;Tonsy et al, 2011;Turan et al, 2012). Jamroz and Kamel (2002) stated that essential oils also improve the fat digestion in broilers.…”
Section: Essential Oilsmentioning
confidence: 99%